2015
DOI: 10.1190/geo2015-0075.1
|View full text |Cite
|
Sign up to set email alerts
|

Phase and amplitude tracking for seismic event separation

Abstract: We have developed a method to decompose seismic records into atomic events, each defined by a smooth phase function and a smooth amplitude function. This decomposition is intrinsically nonlinear and calls for a nonconvex least-squares optimization formulation, along the lines of full-waveform inversion. To overcome the lack of convexity, we have developed an iterative refinement-expansion scheme to initialize and track the phase and amplitude for each atomic event. For short, we called the method phase trackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The problem of (sparse) super-resolution is to recover discrete, point-like objects from their noisy and bandlimited spectral measurements. It arises in many fields such as frequency estimation, sampling theory, array processing, astronomical imaging, seismic imaging, nonuniform FFT, statistics, radar signal detection, error correction codes, and others [4,12,13,16,10,20,28,25,35]. Our main results have direct implications for the problem of super-resolution under sparsity constraints, in the so-called "on-grid" model 2 .…”
Section: Stable Super-resolution Of Point Sourcesmentioning
confidence: 79%
“…The problem of (sparse) super-resolution is to recover discrete, point-like objects from their noisy and bandlimited spectral measurements. It arises in many fields such as frequency estimation, sampling theory, array processing, astronomical imaging, seismic imaging, nonuniform FFT, statistics, radar signal detection, error correction codes, and others [4,12,13,16,10,20,28,25,35]. Our main results have direct implications for the problem of super-resolution under sparsity constraints, in the so-called "on-grid" model 2 .…”
Section: Stable Super-resolution Of Point Sourcesmentioning
confidence: 79%
“…Yet, by posing it as a data processing problem, the nonconvexity can be empirically overcome with an explicit initialization scheme using multiple signal classification (MUSIC), coupled with a careful trust-region "expansion and refinement" scheme to track the smooth phase and amplitude. We refer the reader to the detailed algorithm in the previous paper (Li and Demanet, 2015).…”
Section: Review Of Phase Tracking and Frequency Extrapolationmentioning
confidence: 99%
“…In a previous paper (Li and Demanet, 2015), we demonstrated that there exist interesting physical scenarios, in which low-frequency data can be synthesized from the band-limited field recordings using nonlinear signal processing. This processing step is performed before FWI in the frequency domain.…”
Section: Review Of Phase Tracking and Frequency Extrapolationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to achieve it for particular applications one can try to incorporate the underlying physics and asymptotic analysis to arrive at PPRKS. Our approach is related to other known approaches in the field of oscillatory wave problem computation, such as preconditioners for Helmholtz solvers [14,17], Filon quadrature [19], and a recent approach to data compression using phase-tracking [21].…”
mentioning
confidence: 99%